Advances in the proteomic discovery of novel therapeutic targets in cancer - Guo S; Zou J; Wang G (Dove Medical Press, 2013)
Shanchun Guo,1 Jin Zou,2 Guangdi Wang3 1Department of Microbiology, Biochemistry, and Immunology, Morehouse School of Medicine, 2Center for Cancer Research and Therapeutic Development, Clark Atlanta University, Atlanta, GA, USA; 3Research Centers in Minority Institutions Cancer Research Program, Xavier University of Louisiana, New Orleans, LA, USA Abstract: Proteomic approaches are continuing to make headways in cancer research by helping to elucidate complex signaling networks that underlie tumorigenesis and disease progression. This review describes recent advances made in the proteomic discovery of drug targets for therapeutic development. A variety of technical and methodological advances are overviewed with a critical assessment of challenges and potentials. A number of potential drug targets, such as baculoviral inhibitor of apoptosis protein repeat-containing protein 6, macrophage inhibitory cytokine 1, phosphoglycerate mutase 1, prohibitin 1, fascin, and pyruvate kinase isozyme 2 were identified in the proteomic analysis of drug-resistant cancer cells, drug action, and differential disease state tissues. Future directions for proteomics-based target identification and validation to be more translation efficient are also discussed. Keywords: proteomics, cancer, therapeutic target, signaling network, tumorigenesis